Проблеми сучасного спорту: особливості тендерних стереотипів та можливості їх подолання - Ієвлєв, І. В.; Рябовол, Д. А. (ХНУРЕ, 2019)
The article deals with the current state of the problem of gender stereotypes in sports. Sport as a social institution is an ideal opportunity to study gender stereotypes, especially masculinity and femininity. In the framework of modem gender theory, one of the most promising areas can be considered the study of personal, individual prerequisites for the successful self-realization of women and men in any sport, which excludes the negative impact of gender stereotypes. The main groups of gender stereotypes and the influence of such stereotypes on public consciousness are analyzed